PENGELOLAAN RUANG TERBUKA PUBLIK OLEH KOMUNITAS DI KOTA YOGYAKARTA - , Heny Candra Dewi; , Prof. Ir. Bakti Setiawan, M.A.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The differences in the management of public open space (âPOSâ) in Yogyakarta city by community resulted in different performance of the âPOSâ. The purpose of this research are: (a) to describe the condition of âPOSâ in Yogyakarta city